Peptidomic Analysis of Rat Plasma: Proteolysis in Hemorrhagic Shock. Issue 5 (May 2016) - Aletti, Federico; Maffioli, Elisa; Negri, Armando; Santamaria, Marco H.; DeLano, Frank A.; Kistler, Erik B.; Schmid-Schönbein, Geert W.; Tedeschi, Gabriella
Abstract : ABSTRACT: It has been previously shown that intestinal proteases translocate into the circulation during hemorrhagic shock and contribute to proteolysis in distal organs. However, consequences of this phenomenon have not previously been investigated using high-throughput approaches. Here, a shotgun label-free quantitative proteomic approach was utilized to compare the peptidome of plasma samples from healthy and hemorrhagic shock rats to verify the possible role of uncontrolled proteolytic activity in shock. Plasma was collected from rats after hemorrhagic shock (HS) consisting of 2-h hypovolemia followed by 2-h reperfusion, and from healthy control (CTRL) rats. A new two-step enrichment method was applied to selectively extract peptides and low molecular weight proteins from plasma, and directly analyze these samples by tandem mass spectrometry. One hundred twenty-six circulating peptides were identified in CTRL and 295 in HS animals. Ninety-six peptides were present in both conditions; of these, 57 increased and 30 decreased in shock. In total, 256 peptides were increased or present only in HS confirming a general increase in proteolytic activity in shock. Analysis of the proteases that potentially generated the identified peptides suggests that the larger relative contribution to the proteolytic activity in shock is due to chymotryptic-like proteases. These results provide quantitative confirmation that extensive, system-wide proteolysis is part of the complex pathologic phenomena occurring in hemorrhagic shock.